The effects of a multidimensional treatment programme within a cognitive-behavioural hypnotherapeutic framework for sufferers of Fibromyalgia - Miller, Tania (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.)--Stellenbosch University, 2000.